PATHOGENETIC ASPECTS OF THE FORMATION OF THE PANCREAS PATHOLOGY IN CHILDREN WITH SENSITIZATION TO FOOD ALLERGENS - Karpushenko, J.V. (World of Medicine and Biology, 2013)
The results of research of the pancreas in children with sensitization to food allergens are presented in article. The role of allergic factor in the development of the pathology of the pancreas in children is proven. The scheme of the pathogenesis of the pancreatic diseases in children with food sensitization is engineered.
Keywords: children; pancreas; food sensitization; pathogenesis